Jak autor zdjęć może pomóc aktorowi, czyli Joker od kuchni - Taras, Katarzyna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
The main inspiration of my essay How the cinematographer can help the actor – an insider’s perspective on Joker is Lawrence Sher’s masterclass that took place on 1st December 2020 via Zoom. It was a masterclass for students of the Polish National Film School in Lodz and I had great honor to lead this workshop. In this article, I try to analyze how a cinematographer can help actor to make a great performance. My essay is a “case study” because I focus how cinematographic means create a story and serve the actor who likes to improvise.